Compliance with Anemia Management Indicators Among Maintenance Hemodialysis Patients: A Clinical Audit from a Tertiary Center (Pakistan Journal of Kidney Diseases, 2026)
Background Anemia is a major complication among patients with end-stage renal disease (ESRD) receiving maintenance hemodialysis (MHD). Effective management requires consistent adherence to guideline-recommended practices, including hemoglobin monitoring, iron assessment, and appropriate erythropoiesis-stimulating agent (ESA) titration. This audit aimed to evaluate compliance with key anemia management indicators in a tertiary hemodialysis unit.Methods A cross-sectional clinical audit was conducted among 62 adult MHD patients at Evercare Hospital Dhaka. Data were collected using a structured checklist based on KDIGO 2021 anemia guidelines. Eight indicators were assessed: anemia screening, iron status documentation, correction of iron deficiency, post-ESA hemoglobin monitoring, maintenance of target hemoglobin, quarterly iron profile checks, ESA dose adjustments, and completion of patient education. Compliance levels were analyzed descriptively and compared across genders.Results High compliance (82–100%) was observed in anemia screening, ESA dosing, post-ESA hemoglobin monitoring, and patient education. Hemoglobin maintenance within target ranges showed moderate adherence (62.9%). Iron documentation (35.5%) and quarterly iron monitoring (8.1%) demonstrated critically low compliance. Male patients achieved better hemoglobin control than females (80.8% vs. 50%). A strong positive correlation was found between appropriate ESA titration and hemoglobin stability.Conclusion The audit identified strong adherence to ESA-related processes and patient education but highlighted major gaps in iron assessment and routine monitoring. Strengthening iron management practices is essential to optimize anemia outcomes in MHD patients. Targeted quality-improvement interventions are recommended to enhance overall compliance and align practice with international standards.
Keywords: anemia; compliance; indicators; hemodialysis; clinical audit